An ultra-sensitive photothermal lateral flow immunoassay for 17β-estradiol in food samples. (15th March 2023) - Zhang, Yi; Yang, Han-Jie; Xu, Zhenghua; Liu, Xiao; Zhou, Jie; Qu, Xu-Fang; Wang, Wen-Long; Feng, Yongwei; Peng, Chifang
Highlights: An ultra-sensitive photothermal lateral flow immunoassay strip (LFIA) was established for the detection of 17β-estradiol (E2 ) in food samples. Black phosphorus-gold nanocomposites modified with anti-E2 antibody were applied as photothermal probe which exhibited high photothermal conversion efficiency and achieved high signal-to-noise ratio. The LOD of this established photothermal LFIA was 0.05 ng mL −1, over 100-fold more sensitive than visual LFIA, and a linear range of 3 orders of magnitude from 0.05 ng mL -1 to 50 ng mL -1 was achieved. Abstract: Hormone residues in food and drinking water endanger human health, therefore, on-site analysis techniques of superior performance are important for monitoring this risk. In this study, an ultra-sensitive photothermal lateral flow immunoassay (LFIA) for quantification of 17β-estradiol (E2 ) has been developed. Anti-E2 antibody modified black phosphorus-Au (BP-Au) nanocomposite was developed as a photothermal contrast signal probe and the temperature at test-zone was recorded with an infrared camera. Under the irradiation of 808 nm laser at test-zone, it gave temperatures negatively related to the concentrations of E2 in samples. Under optimal detecting conditions, the developed photothermal LFIA exhibited a limit of detection of 50 pg mL −1, over 100-fold more sensitive than visual LFIA, and a linear range of 3 orders of magnitude. This method has been successfully applied to water, milk, and milk powder samples.